Effectiveness of Nephron Sparing Surgery and Radical Nephrectomy in the Management of Unilateral Wilms Tumor: A Meta-Analysis - Chen, Hongkun; Yang, Shuqing; Qian, Cheng (Frontiers in Oncology, 2020)
Background: Unilateral Wilms tumor is the most common renal malignancy in the pediatric population. Although the onset of surgical intervention like radical nephrectomy has substantially reduced the mortality rate, recent evidence has raised concerns regarding several postoperative complications associated with this procedure. Nephron sparing surgery has been reported to avoid such postoperative complications and have high technical success rate. However, no attempt to date has been made to synthesize the evidence comparing the efficacy of radical nephrectomy and nephron sparing surgery for managing unilateral Wilms tumor. Methods and Results: To metastatistically compare the efficiency of radical nephrectomy with nephron sparing surgery for managing unilateral Wilms tumor, a systematic identification of the literature was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines on four academic databases: MEDLINE, Scopus, EMBASE, and CENTRAL. A meta-analysis comparing renal function (estimated glomerular filtration rate), survival rate, and rate of relapse was performed to compare the efficacy of radical nephrectomy and nephron sparing surgery. Out of 1,283 records, 20 articles including 5,246 children (mean age, 4.3 ± 3.0 years) were included in this review. Radical nephrectomy was performed on 11 of the included studies, whereas nephron sparing surgery was performed on five studies. Two studies compared the efficacy of both interventions. The meta-analysis reveals the beneficial effects of nephron sparing surgery (Hedge's g, 0.76) as compared to radical nephrectomy (−0.16) for the estimated glomerular filtration rate for children with unilateral Wilms tumor. Moreover, higher survivability (0.59) and lesser occurrence of relapse were (−1.0) also reported for cases operated with nephron sparing surgery. Conclusion: The current meta-analysis recommends the use of nephron sparing surgery for unilateral Wilms tumor. The procedure accounts for higher survivability and postoperative renal function and lesser incidence of relapse as compared to radical nephrectomy.